Explorar el desempeño de la tecnología Blockchain en la economía digital (2019)
In the present work of degree a visualization of the development of BLOCKCHAIN technology is made, in the new concept created as digital economy or orange economy, from the revision of new developments and applications to the economy. A descriptive methodology will be used based on the exposure of several authors and their perspectives according to the advantages or disadvantages, which would involve the use of this technology in most conventional and non-conventional industries, therefore the economy will no longer be based on tangible elements, but in the creation and innovation of new market niches and business opportunities, the results of this degree work provide new tools to let international trade flow, data are obtained from industries that have implemented BLOCKCHAIN in their business structure , since in a universe that changes technologically very fast, it requires the ability to allocate resources quickly and efficiently, systems capable of self-organizing and perform transactions, the BLOCKCHAIN seems to be the key to achieve this.